Cubital tunnel syndrome in Noonan syndrome secondary to hypoplasia of the humeral trochlea. (June 2020) - Koike, Mana; Tajika, Tsuyoshi; Kuboi, Takuro; Endo, Fumitaka; Chikuda, Hirotaka
This report describes the case of a 45-year-old woman with Noonan syndrome who developed cubital tunnel syndrome secondary to hypoplasia of the humeral trochlea. Cubital tunnel syndrome, the second-most common peripheral compression neuropathy, is caused by compression of the ulnar nerve at the elbow. Noonan syndrome, an autosomal dominant multisystem disorder, is characterized by variable cognitive deficit and skeletal, ectodermal and hematologic anomalies. Results show three distinctive anatomical features such as (1) hypoplasia of the humeral trochlea and medial epicondyle, (2) absence of the medial intermuscular septum and (3) lack of Osborn's ligament.